Longitudinal patterns of fish assemblages in mountain streams from tropical forest biome - Silva, João Fernando Marques Da; Raio, Cibele Bender [UNESP]; Bernardino, Débora Fernandes Silva; Bennemann, Sirlei Terezinha (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2013)
The aim of this study was to verify structure patterns in fish assemblages in mountain streams of the Rio Tibagi basin through the characterization of spatial and temporal variations in the composition of fish species. Samples were collected in three segments of the Varanal, João Pinheiro and Rio Preto streams. We collected 1154 specimens belonging to 21 species. The most abundant orders were Characiformes (59.01 ± 2.84%) and Siluriformes (39.34 ± 2.82%). Phalloceros harpagos was the most abundant species with 433 individuals, followed by Trichomycterus aff.davisi, with 292 individuals. No temporal variations (between seasons) were detected, but the cluster analysis suggests a separation of species composition between the segments closer to the headwaters and those more distant. The first two axes of the Canonical Correspondence Analysis (CCA) explained 80.09% of the variation in species abundance, and the variables that structured the fish assemblages in those streams were the stream width, depth, water speed, flow rate, conductivity and pH.

O objetivo deste trabalho foi verificar padrões na estrutura de assembleias de peixes nos riachos de montanha da bacia do rio Tibagi através da caracterização de variações espaciais e temporais na composição de espécies de peixes. Foram realizadas coletas em três trechos dos riachos Varanal, João Pinheiro e Rio Preto. No total foram coletadas 21 espécies, em um total de 1154 indivíduos. As ordens mais abundantes foram Characiformes (59,01 ± 2,84%) e Siluriformes (39,34 ± 2,82%). Phalloceros harpagos foi a espécie mais abundante, com 433 indivíduos, seguida por Trichomycterusaff.davisi com 292 indivíduos. Não foi verificada variação temporal (entre estações), mas a análise de agrupamento sugere uma separação na composição de espécies entre os trechos mais próximos das nascentes dos trechos mais afastados. Os dois primeiros eixos da Análise de Correspondência Canônica (CCA) explicaram 80,09% da variação na distribuição em abundância das espécies de peixes, sendo que as variáveis que estruturam a assembleia de peixes nos riachos estudados foram a largura, a profundidade, a velocidade da água, a vazão, a condutividade e o pH dos riachos.
Padrões longitudinais das assembleias de peixes em riachos de montanha pertencentes ao bioma de floresta tropical
Keywords: ichthyofauna; freshwater fishes; neotropical fishes; low order streams; Tibagi river basin; ictiofauna; peixes de água doce; peixes neotropicais; riachos de baixa ordem; bacia do rio Tibagi